The Correlation Between Digital Technology Mastery and Pedagogical Skills of Teachers with Mathematics Learning Outcomes: A Meta-Analysis - Syarifuddin Syarifuddin; Muh. Fitrah; Syarifuddin Syarifuddin (Pusat Publikasi Ilmiah, STKIP Taman Siswa Bima, 2025)
The integration of digital technology in mathematics instruction has become increasingly essential to enhance students’ cognitive engagement and academic outcomes. The purpose of this meta-analysis is to investigate the correlation between digital technology mastery and pedagogical skills of teachers with mathematics learning outcomes published between 2020 and 2024. This quantitative research with a correlation meta-analysis approach utilized a sample of 59 articles published in journals indexed at least in Google Scholar and having a DOI on CrossRef, obtained from journal databases such as Scopus, ERIC, Direct, and Dimensions. Data collection in this research employed the Publish or Perish software and was analyzed using JASP 0.17.3.0 software, assisted by data transformation with Microsoft Excel, aiming to estimate aggregates, draw Forrest plots, and address publication bias. The results of this research indicate that digital technology mastery and pedagogical skills of teachers have a significant influence on students' mathematics learning outcomes, with results free from publication bias and significant variability between studies as evidenced by the correlation value (r) = 0.757. The funnel plot of the 59 studies had varying sample sizes with asymmetric distributions and studies free from potential publication bias strengthened by the plot's display. The research recommends the need to re-evaluate various instruments assessing digital technology mastery and pedagogical skills of teachers to maximize unique variance among the existing variables, and although this study has been generalized, mastery of digital technology and pedagogical skills of teachers can enhance mathematics learning outcomes.